Interdisciplinary Home Visits for Individuals with Advanced Parkinson's Disease and Related Disorders. Issue 6 (2nd April 2018) - Fleisher, Jori; Barbosa, William; Sweeney, Meghan M.; Oyler, Sarah E.; Lemen, Amy C.; Fazl, Arash; Ko, Mia; Meisel, Talia; Friede, Naomi; Dacpano, Geraldine; Gilbert, Rebecca M.; Di Rocco, Alessandro; et al.
Abstract : Parkinson's disease (PD) is a complex, multisymptom, neurodegenerative disease affecting primarily older adults. With progression, many individuals become homebound and removed from coordinated, expert care, resulting in excess morbidity, mortality, and healthcare expenditures in acute care settings and institutions. Home visit care models have achieved the triple aim of improving individual and population health while reducing costs in many frail, community‐dwelling geriatric cohorts. This study details a novel, interdisciplinary home visit program specifically designed for individuals with PD and related disorders and their family caregivers built upon best practice principles in the care of multimorbid older adults. At each quarterly home visit, a movement disorders–trained neurologist, social worker, and nurse work in parallel with the individual and caregiver to complete a history, physical, detailed medication reconciliation, psychosocial needs assessment, and home safety assessment. A comprehensive, person‐centered plan is agreed upon, referrals to community resources are made, standardized documentation is shared, and follow‐up communication is instituted. In the first 2 years, 272 visits were conducted with 85 individuals who represent one of the oldest, most disabled PD populations reported. Satisfaction with and retention in the program were high. This study represents the first translation of the success of interdisciplinary and home‐based geriatric care models to a population with a specific neurological disease. Preliminary evidence supports the need for such programs in vulnerable populations. Future studies will prospectively assess person‐centered outcomes, the effect of using telemedicine on sustainability, and cost effectiveness.